PATIENT CENTERED CARE MODELS: A SYSTEMATIC REVIEW OF IMPLEMENTATION AND IMPACT ON HEALTH OUTCOMES - Ummi Rahmah; Feri Catur Yuliani (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the impact of implementing the model patient-centered care (PCC) on patient satisfaction and involvement in health services. By using the approach systematic literature review, this study analyzes studies measuring the effects of PCC in various care settings. The results showed that implementing PCC significantly increased patient satisfaction and engagement, despite challenges in implementation, such as lack of resources and cultural barriers. The implications of this research provide insight for health care policy and practice to improve service quality through the implementation of a more inclusive and patient-based PCC model.